A computational model of bio-inspired tunable lenses. Issue 6 (2nd November 2018) - Wang, Q.; Cao, Y. J.; Wang, Y. N.; Liu, J. C.; Xie, Y.-X.
Abstract: Bio-inspired tunable lenses are composed of soft dielectric elastomer membranes, clear liquids and rigid frames. Being a new type of optical lens, its focus can be adjusted by the applied voltage. For this type of micro-lens to be practically used in real life, the functional relationship between the voltage and the focus needs to be determined, together with the impact of lens parameters such as the pre-stretching of soft dielectric elastomer membranes, the scale and the volume of liquids on this relationship, as well as on the maximum change of lens focus. In this paper, a compact computational model is proposed based on the assumption of homogeneous deformation and application of energy methods. The model results fit well with the experimental data. By using this model, the relationship curve between the applied voltage and the focus has been given, and it has been verified that such lens will not fail in operation. Finally, by analyzing the three parameters of lens, we can also demonstrate that the pre-stretching of dielectric membranes and the scale affect the relationship between the applied voltage and the focus the most, with the volume of liquids having the least impact.